Pengaruh Media Sosial Instagram @byu.id terhadap Keputusan Pembelian Produk Provider bagi Gen-Z - Setiwi Imrohati; Rosita Anggraini (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2026)
In the digital era, marketing communication strategies through visual platforms are crucial in attracting the interest of young consumers who have critical and dynamic characteristics. This study aims to determine the influence of Instagram social media @Byu.Id on provider product purchasing decisions for Gen-Z. The research approach is quantitative with a survey method. Data were collected through questionnaires distributed to 90 respondents who are followers of the Instagram account @byu.id and are included in the Generation Z age category. The data analysis technique uses simple linear regression analysis to measure the extent to which social media variables influence purchasing decision variables, the study shows that Instagram social media @byu.id has a significant and positive influence on product purchasing decisions. Price, motivation, Choice of purchasing channels, brands, and advertisements in the @byu.id account are proven to be able to stimulate the stage of recognizing needs to purchasing actions in Gen-Z. This study confirms that Instagram social media optimization is a vital instrument for cellular providers in winning the market in the Generation Z segment. After conducting research activities on the influence of Instagram social media @byu.id on provider product purchasing decisions for Gen-Z, there is an influence of Instagram social media @byu.id on provider product purchasing decisions for Gen-Z based on the answers to the statement questions that have been filled in by respondents which are processed through a simple linear regression test, T test and Determination Coefficient. Then there is a very strong relationship between variable X and variable Y which is carried out in the Correlation test, thus there is a very strong influence on provider product purchasing decisions for Gen-Z